2009
DOI: 10.2337/db08-0254
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin Receptor–Mediated Signal Transduction and Tissue Renin-Angiotensin System Contribute to Diabetes-Induced Retinal Inflammation

Abstract: OBJECTIVEThe term “receptor-associated prorenin system” (RAPS) refers to the pathogenic mechanisms whereby prorenin binding to its receptor dually activates the tissue renin-angiotensin system (RAS) and RAS-independent intracellular signaling via the receptor. The aim of the present study was to define the association of the RAPS with diabetes-induced retinal inflammation.RESEARCH DESIGN AND METHODSLong-Evans rats, C57BL/6 mice, and angiotensin II type 1 receptor (AT1-R)-deficient mice with streptozotocin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 50 publications
8
149
1
Order By: Relevance
“…In this study, we investigated localisation and expression of (P)RR in fibrovascular tissues and vitreous fluids from patients with PDR and evaluated the molecular mechanisms in vitro to confirm ideas about (P)RR from previous animal studies [14,[17][18][19][20][21]. We herein report the first evidence of a close association between (P)RR and angiogenic activity in human PDR.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In this study, we investigated localisation and expression of (P)RR in fibrovascular tissues and vitreous fluids from patients with PDR and evaluated the molecular mechanisms in vitro to confirm ideas about (P)RR from previous animal studies [14,[17][18][19][20][21]. We herein report the first evidence of a close association between (P)RR and angiogenic activity in human PDR.…”
Section: Introductionmentioning
confidence: 57%
“…Endothelial localisation of (P)RR in human PDR fibrovascular tissues (P)RR localisation to retinal vessels was previously demonstrated in rodents [14,17,19,29]; however, no studies on human ocular tissue have been reported. First, we confirmed mRNA expression of (P)RR and RAS compo- (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…145 In cultured mesangial cells, it has been suggested that high glucose-induced prorenin upregulation leads to the production of inflammatory cytokines, such as interleukin-1b and cyclooxygenase-2 (Huang and Siragy 146 ). In the retinal vasculature of diabetic mice, Satofuka et al 147 have shown that handle region peptides, also called (P)RR blockers (PRRBs), reduced leukostasis to a greater extent than the AT1-R blocker losartan in wild-type mice and also reduced leukostasis in AT1A receptor gene knockout mice. Furthermore, PRRB reduced the diabetes-induced elevation in retinal expression of phosphorylated extracellular signal-regulated kinases 1/2 in AT1A receptor gene knockout mice.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…Recently, Matavelli et al 95 extended these mechanisms suggesting that the renal (pro)renin and (P)RR axis promotes diabetic nephropathy by significantly increasing the amounts of pro-inflammatory cytokines. The handle region peptide (HRP), a putative blocker of the (P)RR, could efficiently block glomerulosclerosis, 86,88,95,96 while RAS inhibitors were unable to prevent end-stage organ damage associated with diabetes. 97,98 However, not all investigators were able to reproduce the inhibitory effects of HRP either in vivo or in vitro.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 99%